2000
DOI: 10.12968/denu.2000.27.3.132
|View full text |Cite
|
Sign up to set email alerts
|

Malignant Lymphoma of the Maxillary Sinus Masquerading as an Odontogenic Infection: Report of a Case

Abstract: The dental surgeon can play an important role in the early referral of malignancy of the maxillary sinus, and should be familiar with the signs and symptoms of disease of the paranasal sinuses. Here we report a case of a 71-year-old male patient diagnosed with high-grade B-cell lymphoma of the maxillary sinus that was initially thought to be an odontogenic infection. We discuss the signs and symptoms of lymphomas and malignancy of the maxillary sinus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…The extent of the tumor mass was similar to our case, but the type of lymphoma was only defined as B-cell high-grade non-Hodgkin's lymphoma. The significance of the case is that the initial symptoms mimicked the appearance of odontogenic inflammation as in our patient, for which tooth extraction was performed [25]. In the second case, described by Doumas et al, a rapid growth was observed, and the patient's temporal swelling increased rapidly within 10 days after onset, with the development of blurred and double vision in the left eye during the 2 weeks of antibiotic therapy, and exophthalmia and facial paresis within the following 15 days [9].…”
Section: Discussionmentioning
confidence: 55%
See 2 more Smart Citations
“…The extent of the tumor mass was similar to our case, but the type of lymphoma was only defined as B-cell high-grade non-Hodgkin's lymphoma. The significance of the case is that the initial symptoms mimicked the appearance of odontogenic inflammation as in our patient, for which tooth extraction was performed [25]. In the second case, described by Doumas et al, a rapid growth was observed, and the patient's temporal swelling increased rapidly within 10 days after onset, with the development of blurred and double vision in the left eye during the 2 weeks of antibiotic therapy, and exophthalmia and facial paresis within the following 15 days [9].…”
Section: Discussionmentioning
confidence: 55%
“…The most frequent symptoms of NHL arising within the maxillary sinus are pain, swelling, nasal obstruction, paresthesia and numbness [25,30]. The patient had few or no typical complaints, suggesting the presence of periapical inflammation and maxillary sinusitis localized to the left upper premolar region; therefore, a definitive diagnosis was hardly determinable.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation